SOCIALIZATION OF LAW NUMBER 7 OF 2012 ABOUT MANAGING OF SOCIAL CONFLICTS AS EFFORTS TO CREATE A HARMONIOUS ENVIRONMENT IN GENTENG VILLAGE, SUKASARI SUBDISTRICT SUMEDANG REGENCY - Soni Akhmad Nulhaqim; Muhammad Fedryansyah; Eva Nuriyah Hidayat (Jurnal Kolaborasi Resolusi Konflik, 2020)
ABSTRAKCommunity Service Activities (PPM) in Genteng Village, Sukasari Subdistrict, Sumedang Regency was initiated because the agrarian conflict had happened in that location. The conflict resolution were relatively slow due to the lack of understanding, knowledge and skills of the actors in conducting conflict resolution. In contrary, conflict resolution is clearly written inLaw Number 7 of 2012 about Managing of Social Conflict. In addition, the location of PPM also has a high potential for conflicts, especially conflicts in the useof natural resources. This must be anticipated by encouraging existing communities and local institutions to worktogether to prevent conflict and create a harmonious environment. The purpose of this PPM activity is to increase the knowledge, understanding and skills of target groups in conducting conflict resolution based on Law No. 7 of 2012 about Managing of Social Conflict, to increasethe knowledge, understanding and skills of target groups in conducting community-based conflict resolution and to encourage target groups to prevent conflicts andcan creat a harmony in the village. The target groups in this PPM activity are the farming community, village government and local institutions in the Genteng Village. The method of implementing PPM activities was conducted in several stages, such as the preparation phase, the assessment stage, the plan of treatment stage, and the activity implementation stage.